2010
DOI: 10.1007/s10531-010-9895-9
|View full text |Cite
|
Sign up to set email alerts
|

Polylepis woodland remnants as biodiversity islands in the Bolivian high Andes

Abstract: Mountain forests deserve special attention from ecologists and conservation biologists given the ecosystem services they provide to society, and their threat under global change. In the subalpine region of the Andes, Polylepis woodlands occur as arboreal islands in a matrix of grassland and scrub. Due to overgrazing and burning, however, these woodland patches are believed to cover only 11% of their potential area in Bolivia, core area for Polylepis. We reviewed the knowledge on the species diversity for the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 47 publications
1
51
0
17
Order By: Relevance
“…One unique Andean ecosystem, nestled in the humid and dry Puna along the Andes, is the Polylepis forest (Simpson, 1979; Simpson, 1986; Kessler, 2006). Considered as one of the world’s highest elevation forests (Gareca et al, 2010), it represents a center of avian diversity (Fjeldså et al, 1996; Fjeldså, 2002) and endemism (Fjeldså, Lambin & Mertens, 1999; Fjeldså, 1993), with several birds restricted to this specific ecosystem (Fjeldså & Kessler, 2004; Gareca et al, 2010; Lloyd, 2008a; Lloyd, 2008b; Lloyd, 2008c; Lloyd & Marsden, 2008). According to Fjeldså (2002), 214 bird species use Polylepis forest along the entire range of the Andes, 51 of which are strongly associated to Polylepis and 14 that are highly specialized.…”
Section: Introductionmentioning
confidence: 99%
“…One unique Andean ecosystem, nestled in the humid and dry Puna along the Andes, is the Polylepis forest (Simpson, 1979; Simpson, 1986; Kessler, 2006). Considered as one of the world’s highest elevation forests (Gareca et al, 2010), it represents a center of avian diversity (Fjeldså et al, 1996; Fjeldså, 2002) and endemism (Fjeldså, Lambin & Mertens, 1999; Fjeldså, 1993), with several birds restricted to this specific ecosystem (Fjeldså & Kessler, 2004; Gareca et al, 2010; Lloyd, 2008a; Lloyd, 2008b; Lloyd, 2008c; Lloyd & Marsden, 2008). According to Fjeldså (2002), 214 bird species use Polylepis forest along the entire range of the Andes, 51 of which are strongly associated to Polylepis and 14 that are highly specialized.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional measures of biodiversity (e.g., species richness and diversity indices that include evenness) are commonly used together with Red Lists to understand how species and assemblages are being threatened by human activities [19], [20]. However, so far we have no evidence on whether Red Lists are able to protect species’ ecological traits and evolutionary history, and how this inability affects conservation planning [11], [16], [17], [21][25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Byers (2000) found relatively stable margins for forest edges in the Cordillera Blanca; Coblentz and Kintz (2008) documented relatively little change in forest patches in southern Ecuador in terms of forest edges and hence patch location, size, and shape; and the forest patches studied by Jameson and Ramsay (2007) in southern Peru were similar in size over 50 years, although they became less dense. Many of the studies in the Andes implicate a complicating role of land use, with loss of forest due to burning (Cierjacks et al 2008), and with less habitat available for specialist forest species (Lloyd 2008, Gareca et al 2010, Tinoco et al 2013). Hensen and colleagues (2012) showed that topographic barriers and human-caused habitat fragmentation are both constraining the genetic diversity of Polylepis incana in Ecuador.…”
Section: Dynamics Of Woody Plantsmentioning
confidence: 99%